Determination of the shear traction-separation law of adhesive layers using the end-notched flexure specimen - Morais, Alfredo Manuel Balacó de (2021)
Cohesive zone modelling is increasingly applied to predict the strength of structural adhesive joints. A method is here proposed to determine the bondline shear traction-separation law needed for cohesive zone models. The method combines an effective crack length approach derived from a beam model and an existing J-integral analysis of the end-notched flexure specimen. The resulting work done by the tractions versus separation curves can be easily processed with direct or mixed direct-inverse approaches. Application to some published experimental results demonstrates the potential of the method while highlighting the importance of adherend material and specimen geometry selection.